Development of Novel and Efficient Processes for the Synthesis of 5-Amino and 5-Iminoimidazo[1,2-a]imidazoles via Three-Component Reaction Catalyzed by Zirconium(IV) Chloride - Driowya, Mohsine; Guillot, Régis; Bonnet, Pascal; Guillaumet, Gérald (Frontiers in Chemistry, 2019)
General and efficient approaches for the synthesis of new 5-amino and 5-iminoimidazo[1,2-a]imidazoles were developed through a three-component reaction of 1-unsubstituted 2-aminoimidazoles with various aldehydes and isocyanides mediated by zirconium(IV) chloride. The protocols were established considering the reactivity of the starting substrate, which varies depending on the presence of a substituent on the 2-aminoimidazole moiety. A library of new N-fused ring systems with wide structural diversification, novel synthetic, and potential pharmacological interest was obtained in moderate to good yields.